2017
DOI: 10.1016/j.rbmo.2016.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic application of oxidation-reduction potential assay for measurement of oxidative stress: clinical utility in male factor infertility

Abstract: The objectives of this study were to: (i) describe a protocol measuring the oxidation-reduction potential (ORP) by MiOXSYS System as an alternative method of seminal oxidative stress (OS) testing; (ii) establish a reference value for static ORP (sORP) to distinguish between controls and male factor infertility patients; (iii) evaluate intra-observer and inter-observer reliability; and (iv) examine association of sORP with sperm parameters predictive of male factor infertility. Elevated levels of sORP were seen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
101
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(111 citation statements)
references
References 43 publications
7
101
0
3
Order By: Relevance
“…A higher ORP level indicated an imbalance in the activity of all available oxidants relative to all available antioxidants in the ejaculate and indicates a state of oxidative stress. Agarwal et al confirmed the cutoff level as 1.36 mV/10 6 spermatozoa/mL [83]. This MiOXSYS system has shown promise as a diagnostic tool in the evaluation of male infertility.…”
Section: Measurement Of Ros In Human Semenmentioning
confidence: 92%
“…A higher ORP level indicated an imbalance in the activity of all available oxidants relative to all available antioxidants in the ejaculate and indicates a state of oxidative stress. Agarwal et al confirmed the cutoff level as 1.36 mV/10 6 spermatozoa/mL [83]. This MiOXSYS system has shown promise as a diagnostic tool in the evaluation of male infertility.…”
Section: Measurement Of Ros In Human Semenmentioning
confidence: 92%
“…[86] They confirmed the presence of significantly higher levels of ORP among the infertile group and demonstrated, using receiver operator curve analysis, that a cut-off level of 1.36 mv//10 6 sperm/ml was associated with a sensitivity of 69.6%, specificity of 83.1%, and overall accuracy of 75.2% (area under the curve = 0.770). [86]…”
Section: Assessment Of Seminal Oxidative Stressmentioning
confidence: 85%
“…По данным ряда авторов, окислительный стресс наблюдается приблизительно у половины мужчин с подтверждён-ным бесплодием [3,10,13,14,17].…”
Section: в настоящее время отмечается отчётливая тенденция снижения рunclassified
“…Нарушение структуры плазматической митохондриальной мембраны меняет её текучесть, что снижает подвижность сперматозоидов и изме-няет акросомальную реакцию, необходимую для про-никновения сперматозоида в оболочку яйцеклетки [2,4,5,13,15,16].…”
Section: в настоящее время отмечается отчётливая тенденция снижения рunclassified